High-performance copper-iron-niobium composite material and preparation method thereof
Patent Information
- Application Number
- CN202611472503.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-21
- Publication Date
- 2026-11-03
AI Technical Summary
During the melting and solidification process, the iron-rich phase in Cu-Fe composites is prone to segregation and coarsening, which leads to a decline in the mechanical and processing properties of the alloy, and existing methods are difficult to effectively suppress this.
High-performance copper-iron-niobium composite materials were prepared using ball milling, hot isostatic pressing, cladding extrusion, and drawing processes. By adding Nb, the grain size was refined and the ability of the iron-rich phase and the matrix to coordinate deformation was improved.
It significantly inhibits the growth and coarsening of the iron-rich phase, improves the overall performance of the alloy, and significantly enhances tensile strength and electrical conductivity, achieving a good match between strength and electrical conductivity.
Smart Images

Figure CN123027474A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of high-performance copper-based composite materials, and relates to a high-performance copper-iron-niobium composite material and its preparation method. Background Technology
[0002] Cu-Fe composite materials generally refer to a class of copper alloys with an iron content greater than 5%. Cu-Fe composite materials not only possess the high electrical and thermal conductivity of Cu, but also the soft magnetism, high strength, and high stiffness of Fe. They also have unique electromagnetic shielding properties and a relatively low cost advantage, and are currently widely used in high-precision fields such as pulsed strong magnetic field systems, particle accelerator electromagnetic transmitters, and high-energy synchrotron radiation sources.
[0003] However, due to its high iron content, Cu-Fe composites are prone to segregation and coarsening of the iron-rich phase during smelting and solidification, resulting in severe macroscopic segregation and a decline in the alloy's mechanical and processing properties. Powder metallurgy can suppress segregation to some extent, but how to further suppress the growth and coarsening of the iron-rich phase and improve the coordinated deformation ability between the iron-rich phase and the copper matrix remains a pressing technical problem to be solved in this field. Summary of the Invention
[0004] In view of this, the purpose of the present invention is to provide a high-performance copper-iron-niobium composite material and its preparation method, so as to reduce the segregation of iron in the copper matrix, inhibit the growth and coarsening of the iron-rich phase, improve the coordinated deformation ability of the iron-rich phase and the copper matrix, thereby improving the comprehensive performance of the copper-iron composite material.
[0005] To achieve the above objectives, the present invention provides the following technical solution: A high-performance copper-iron-niobium composite material, comprising the following components by weight percentage: Fe 5-10%, Nb 0.5-2%, with the balance being Cu and impurities.
[0006] Furthermore, by weight percentage, it contains the following components: Fe 10%, Nb 1%, with the balance being Cu and impurities.
[0007] As a general inventive concept, the present invention also provides a method for preparing the high-performance copper-iron-niobium composite material as described above, comprising the following steps: S1. Ball milling: Copper powder, iron powder and niobium powder are mixed and stirred evenly using a planetary ball mill to obtain a mixed powder; S2, Hot Isostatic Pressing: The mixed powder obtained in step S1 is loaded into a stainless steel sleeve, compacted and degassed, and then subjected to hot isostatic pressing. The stainless steel sleeve is removed by turning to obtain a copper-iron-niobium composite ingot. S3. Encasing extrusion: The copper-iron-niobium composite ingot obtained in step S2 is heated and kept at a constant temperature and then extruded to obtain copper-iron-niobium composite rods. S4. Drawing: The copper-iron-niobium composite rod obtained in step S3 is drawn in multiple passes in a single-die wire drawing machine to obtain copper-iron-niobium composite wire. S5. Aging: The copper-iron-niobium composite wire obtained in step S4 is subjected to aging treatment to obtain a high-performance copper-iron-niobium composite wire.
[0008] Furthermore, in step S1, the ball milling time is 12 to 96 hours, the ball-to-material ratio is 5:1 to 20:1, the rotation speed is 200 to 500 rpm, and argon gas is introduced throughout the process to prevent oxidation.
[0009] Furthermore, in step S2, the outer diameter of the stainless steel sheath is 80-100 mm, the wall thickness is 10-15 mm, and the filling coefficient inside the sheath is 96%-98%.
[0010] Furthermore, in step S2, the hot isostatic pressing temperature is 900–1300℃, the holding time is 2–8h, and the load is 150–200MPa.
[0011] Furthermore, in step S3, the extrusion holding temperature is 900-950℃, the holding time is 1-3h, the extrusion ratio is 25-70, and graphite oil is used as the extrusion lubricant.
[0012] Furthermore, in step S4, the deformation amount of each drawing pass is 5-20%, and the drawing speed is 2-8 m / min.
[0013] Furthermore, in step S5, the aging temperature is 300–500℃, the aging time is 15–720 min, the aging heat treatment is carried out in a muffle furnace, and charcoal protection is used throughout the process to prevent oxidation.
[0014] The beneficial effects of this invention are as follows: This invention utilizes planetary ball milling, hot isostatic pressing, and cladding extrusion to prepare alloys, effectively avoiding the problem of iron segregation in copper-iron alloys during the smelting process. It also significantly inhibits the growth and coarsening of precipitated phases, refines grains, promotes the dispersed and fine distribution of iron-rich phases, and improves the overall performance of the alloy. This invention incorporates Nb into a copper-iron alloy, which improves the coordinated deformation capability between the iron-rich phase and the matrix during extrusion and strengthens the copper matrix through load transfer. Examples show that the copper-iron-niobium composite wire prepared by this invention achieves a tensile strength of 685 MPa, a conductivity of 58% IACS, and an elongation of 12.3%, achieving a good balance between strength and conductivity.
[0015] Other advantages, objectives, and features of the invention will be set forth in part in the description which follows, and in part will be apparent to those skilled in the art from the following examination, or may be learned from practice of the invention. The objectives and other advantages of the invention can be realized and obtained through the following description. Attached Figure Description
[0016] To make the objectives, technical solutions, and advantages of the present invention clearer, the preferred embodiments of the present invention will be described in detail below with reference to the accompanying drawings, wherein: Figure 1 This is a process flow diagram of the preparation method of the high-performance copper-iron-niobium composite material of the present invention; Figure 2 This is a cross-sectional schematic diagram of the stainless steel packaging assembly structure in an embodiment of the present invention; Figure 3 This is a schematic diagram of the multi-pass drawing process in an embodiment of the present invention; Figure 4 Metallographic images of the mixed powder of copper powder, iron powder and niobium powder in Example 1 of the present invention after ball milling for different times. Detailed Implementation
[0017] The following specific examples illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and various details in this specification can be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the illustrations provided in the following embodiments are only schematic representations of the basic concept of the present invention. Unless otherwise specified, the following embodiments and features can be combined with each other.
[0018] The preparation method of the high-performance copper-iron-niobium composite material of the present invention includes the following steps: S1. Ball milling: Weigh copper powder, iron powder, and niobium powder according to the formula, mix and stir evenly using a planetary ball mill to obtain a mixed powder; wherein, by weight percentage, the raw material components are: Fe 5-10%, Nb 0.5-2%, with the balance being Cu and impurities; the ball milling time is 12-96 hours, the ball-to-material ratio is 5:1-20:1, the rotation speed is 200-500 rpm, and argon gas is introduced throughout the process to prevent oxidation.
[0019] S2. Hot Isostatic Pressing: The mixed powder obtained in step S1 is loaded into a stainless steel sleeve, compacted and degassed, and then subjected to hot isostatic pressing. The stainless steel sleeve is removed by turning to obtain a copper-iron-niobium composite ingot. The outer diameter of the stainless steel sleeve is 80-100 mm, the wall thickness is 10-15 mm, and the filling coefficient inside the sleeve is 96%-98%. The hot isostatic pressing temperature is 900-1300℃, the holding time is 2-8 h, and the load is 150-200 MPa.
[0020] S3. Encasing Extrusion: The copper-iron-niobium composite ingot obtained in step S2 is heated and kept at a certain temperature before being extruded to obtain copper-iron-niobium composite rods; wherein, the extrusion holding temperature is 900-950℃, the holding time is 1-3h, the extrusion ratio is 25-70, and the extrusion lubricant is graphite oil.
[0021] S4. Drawing: The copper-iron-niobium composite rod obtained in step S3 is drawn in multiple passes in a single-die wire drawing machine to obtain copper-iron-niobium composite wire; wherein the deformation amount per drawing pass is 5-20%, and the drawing speed is 2-8 m / min.
[0022] S5. Aging: The copper-iron-niobium composite wire obtained in step S4 is subjected to aging treatment to obtain high-performance copper-iron-niobium composite wire; wherein, the aging temperature is 300-500℃, the aging time is 15-720min, the aging heat treatment is carried out in a muffle furnace, and charcoal protection is used throughout the process to prevent oxidation.
[0023] Figure 2 A cross-sectional view of the assembly structure of a stainless steel package. Figure 2 As shown, the mixed powder is filled into a stainless steel sleeve, and the two ends of the stainless steel sleeve are sealed by an upper end plug and a lower end plug, respectively. After filling, the mixed powder is compacted and degassed, and then subjected to hot isostatic pressing in step S2.
[0024] Figure 3 This is a schematic diagram of a multi-stage drawing process. (For example...) Figure 3 As shown, in step S4, the copper-iron-niobium composite bar passes through multiple drawing dies in sequence along the drawing direction, and after multiple passes of diameter reduction, a copper-iron-niobium composite wire with the target diameter is obtained.
[0025] Example 1 The copper-iron-niobium composite material of this embodiment contains the following components by weight percentage: Fe 10%, Nb 1%, with the balance being Cu and impurities. Its preparation process is as follows: Figure 1 As shown, the specific steps include: S1. Ball milling: Weigh out 89 wt.% of electrolytic copper powder, 10 wt.% of reduced iron powder, and 1 wt.% of niobium powder, all with a purity of not less than 99.9%. All three powders should pass through a 200-mesh sieve. Place the weighed powders into the stainless steel ball mill jar of a planetary ball mill. Use zirconia grinding balls as the grinding medium, with a ball-to-material ratio of 10:1, a rotation speed of 300 rpm, and a ball milling time of 96 hours. Argon gas is introduced throughout the ball milling process to prevent powder oxidation, resulting in a mixed powder.
[0026] Metallographic images of the mixed powder obtained in this step after ball milling for different times are shown below. Figure 4 As shown. By Figure 4 It can be seen that as the ball milling time increases, the iron and niobium powder particles in the mixed powder are gradually broken down and refined, and their distribution in the copper powder matrix tends to be uniform, laying the foundation for obtaining a dispersed iron-rich phase in the future.
[0027] S2. Hot Isostatic Pressing: The mixed powder obtained in step S1 is loaded into a stainless steel sleeve in several batches and compacted by vibration. A cross-sectional schematic diagram of the sleeve assembly structure is shown below. Figure 2 As shown; the stainless steel sheath has an outer diameter of 90mm, a wall thickness of 10mm, and a filling coefficient of 96.8%; after filling with powder, the sheath is connected to a vacuum system via a degassing tube, and a vacuum is drawn until the internal pressure of the sheath does not exceed 10. - The pressure and temperature are simultaneously increased to 400-500℃ and maintained for more than 2 hours to fully remove the gas and moisture adsorbed by the powder. Then the degassing tube is sealed by welding. The sealed casing is placed in a hot isostatic pressing equipment, heated and pressurized to 1000℃ and 160MPa, and held for 4 hours. After cooling with the furnace, it is taken out and the stainless steel casing is removed by turning to obtain a copper-iron-niobium composite ingot.
[0028] S3. Encasing and extrusion: The copper-iron-niobium composite ingot obtained in step S2 is placed in a resistance furnace and heated to 900°C and held for 2 hours. Then, it is extruded with an extrusion ratio of 64. Graphite oil is used as the extrusion lubricant. After extrusion, it is air-cooled to obtain a copper-iron-niobium composite rod with a diameter of 10 mm.
[0029] S4. Drawing: The copper-iron-niobium composite rod obtained in step S3 is drawn in multiple passes on a single-die wire drawing machine. A schematic diagram of the drawing process is shown below. Figure 3 As shown, emulsion lubrication is used throughout the drawing process, and the deformation per pass is controlled in stages according to the wire diameter: when drawing a 10mm diameter bar to a 5mm diameter, the deformation per pass is 10% to 20%; when drawing to a 3mm diameter, the deformation per pass is 5% to 15%; the drawing speed is 2 to 8m / min, and finally a copper-iron-niobium composite wire with a diameter of 3mm is obtained.
[0030] S5. Aging: The copper-iron-niobium composite wire obtained in step S4 is buried in a refractory container filled with charcoal powder and placed in a muffle furnace to be kept at 300℃ for 2 hours for aging treatment. Charcoal is used for protection throughout the process to prevent oxidation. Then, the wire is cooled to room temperature with the furnace to obtain high-performance copper-iron-niobium composite wire.
[0031] Example 2 This embodiment uses a traditional smelting and casting process to prepare copper-iron-niobium composite wire, and its composition is the same as that in Example 1. The specific steps include: (1) Smelting and casting: Prepare 89wt.% electrolytic copper plate, 10wt.% pure iron and 1wt.% pure niobium particles, grind them, ultrasonically clean them and dry them, put them into a vacuum smelting furnace, evacuate the furnace until the pressure inside the furnace is not higher than 10Pa and then heat them. After all the metal is melted, keep it at 1450~1500℃ for 10min. The mold is not preheated. After casting, it is water cooled to obtain an ingot with a diameter of 80mm. (2) Extrusion: The ingot obtained in step (1) is heated and kept at a temperature of 900℃ for 2 hours and the extrusion ratio is 64. After extrusion, it is air-cooled to obtain a copper-iron-niobium composite rod with a diameter of 10mm. (3) Drawing: The copper-iron-niobium composite rod obtained in step (2) is drawn in multiple passes in a single-die wire drawing machine. The deformation amount of each drawing is 5% to 20%, and the drawing speed is 2 to 8 m / min. Finally, a copper-iron-niobium composite wire with a diameter of 3 mm is obtained. (4) Aging: The copper-iron-niobium composite wire obtained in step (3) is placed in a muffle furnace and kept at 300°C for 2 hours to obtain the cast copper-iron-niobium composite wire.
[0032] Example 3 The only difference between this embodiment and Embodiment 1 is that niobium powder is not added to the raw materials; that is, 90 wt.% copper powder and 10 wt.% iron powder are used as raw materials. The remaining process steps and parameters are the same as in Embodiment 1, and copper-iron composite wire is obtained.
[0033] Performance Testing: At room temperature, the tensile strength and elongation of the wires prepared in Examples 1 and 2-3 were tested according to GB / T 228.1-2021 "Metallic Materials - Tensile Testing - Part 1: Room Temperature Test Method". The volume resistivity of the wires was tested according to GB / T 351-2019 "Methods for Measurement of Resistivity of Metallic Materials" and converted to conductivity according to the International Standard for Annealed Copper (%IACS). The test results are shown in Table 1.
[0034] Table 1
[0035] As shown in Table 1, compared with the traditional casting process (Example 2), the tensile strength of the wire prepared by the powder metallurgy process of the present invention increased from 484 MPa to 685 MPa, and the conductivity increased from 50% IACS to 58% IACS. This indicates that the preparation process of the present invention effectively suppressed the segregation and coarsening of the iron-rich phase and significantly improved the comprehensive performance of the alloy. Compared with Example 3 without the addition of Nb, the tensile strength of Example 1 increased from 552 MPa to 685 MPa. This indicates that the addition of Nb further enhanced the mechanical properties of the alloy by improving the coordinated deformation ability of the iron-rich phase and the matrix and the load transfer effect.
[0036] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.
Claims
1. A high-performance copper-iron-niobium composite material, characterized in that: It contains the following components by weight percentage: Fe 5-10%, Nb 0.5-2%, with the balance being Cu and impurities.
2. The high-performance copper-iron-niobium composite material according to claim 1, characterized in that: It contains the following components by weight percentage: Fe 10%, Nb 1%, with the balance being Cu and impurities.
3. A method for preparing a high-performance copper-iron-niobium composite material as described in claim 1 or 2, characterized in that, Includes the following steps: S1. Ball milling: Copper powder, iron powder and niobium powder are mixed and stirred evenly using a planetary ball mill to obtain a mixed powder; S2, Hot Isostatic Pressing: The mixed powder obtained in step S1 is loaded into a stainless steel sleeve, compacted and degassed, and then subjected to hot isostatic pressing. The stainless steel sleeve is removed by turning to obtain a copper-iron-niobium composite ingot. S3. Encasing extrusion: The copper-iron-niobium composite ingot obtained in step S2 is heated and kept at a constant temperature and then extruded to obtain copper-iron-niobium composite rods. S4. Drawing: The copper-iron-niobium composite rod obtained in step S3 is drawn in multiple passes in a single-die wire drawing machine to obtain copper-iron-niobium composite wire. S5. Aging: The copper-iron-niobium composite wire obtained in step S4 is subjected to aging treatment to obtain a high-performance copper-iron-niobium composite wire.
4. The method for preparing the high-performance copper-iron-niobium composite material according to claim 3, characterized in that: In step S1, the ball milling time is 12 to 96 hours, the ball-to-material ratio is 5:1 to 20:1, the rotation speed is 200 to 500 rpm, and argon gas is introduced throughout the process to prevent oxidation.
5. The method for preparing the high-performance copper-iron-niobium composite material according to claim 3, characterized in that: In step S2, the outer diameter of the stainless steel sheath is 80-100 mm, the wall thickness is 10-15 mm, and the filling coefficient inside the sheath is 96%-98%.
6. The method for preparing the high-performance copper-iron-niobium composite material according to claim 3, characterized in that: In step S2, the hot isostatic pressing temperature is 900–1300℃, the holding time is 2–8h, and the load is 150–200MPa.
7. The method for preparing the high-performance copper-iron-niobium composite material according to claim 3, characterized in that: In step S3, the extrusion holding temperature is 900-950℃, the holding time is 1-3h, the extrusion ratio is 25-70, and graphite oil is used as the extrusion lubricant.
8. The method for preparing the high-performance copper-iron-niobium composite material according to claim 3, characterized in that: In step S4, the deformation amount of each drawing pass is 5-20%, and the drawing speed is 2-8 m / min.
9. The method for preparing the high-performance copper-iron-niobium composite material according to claim 3, characterized in that: In step S5, the aging temperature is 300–500℃, the aging time is 15–720 min, the aging heat treatment is carried out in a muffle furnace, and charcoal protection is used throughout the process to prevent oxidation.
10. The high-performance copper-iron-niobium composite material according to claim 1, characterized in that: It contains the following components by weight percentage: Fe 8-10%, Nb 0.8-1.5%, with the balance being Cu and impurities.
